Procedures for standard evaluation and data management of advanced potato clones. Summary guide to selecting potato clones for drought tolerance under field conditions international cooperators’ guide - Cevallos, D.; Souza, J. de; Salas, E.; Eyzaguirre, R.; Bonierbale, Merideth W. (International Potato Center, 2020)
Drought stress is a multidimensional stress and generally leads to changes in the physiological, morphological, ecological, biochemical, and molecular traits of plants (Farooq et al., 2009). In addition, it can negatively affect the quantity and quality of plant growth and yield (Zlatev and Lidon, 2012). Many plants have developed resistance mechanisms to tolerate drought stress, but these mechanisms are varied and depend on plant species (Hossain et al., 2016). There are several options for drought tolerance mechanisms in plants, including developmental, physiological, morphological, ecological, biochemical, and molecular mechanisms. Typically, the mechanisms involved in plant tolerance to drought follow a general plan: maintaining cell water homeostasis under drought conditions (Hossain et al., 2016). Impact of abiotic stresses on potato production will increase over the next decades, due to climate change and the extension of potato cultivation under drought/heat conditions (Hijmanns, 2003) since potato is extremely susceptible to drought (Monneveux et al., 2013). Plant adaptation to drought involves several different morphological and physiological characteristics; however, no specific traits have been reported since drought responses change according to plant genotype and growth stage. Stem height, number of green leaves and leaf length are considered to be the parameters most sensitive to moderate drought conditions (Deblonde and Ledent, 2001); however, these traits have shown inconsistency in many cases. In the present protocol, a selection of traits is shown as a result of previous experiments and exhaustive data analysis at the International Potato Center.